Enhancing the classroom acoustic environment in Badr University, Egypt: A case study. Issue 4 (December 2022) - Selim, Ahmed M; Saeed, Doha M
The acoustic environment of the classroom is deemed significant to enhance the learning quality and the learning outcomes. Noise exposure levels and reverberation are the main acoustic parameters to consider in the classroom because it affects speech intelligibility. As a result of the modern teaching methods especially in the practical faculties. Workgroup activities have become a common tool for learning, it has a higher noise level than independent work. Therefore, the specialists become face a great challenge to achieve acoustic comfort in classrooms. In spite of that, in Egypt, acoustic conditions are rarely implemented into classroom design practice. This study evaluated the acoustic performance of a typical classroom in Badr University, Egypt in unoccupied condition for four cases. Unoccupied ambient noise level (ANLs) and reverberation time (RTs) were measured by using Testo 815 device, and Ecotect software. Additionally, the measurements were compared with the standards and norms. Acoustic treatments using absorbent materials were suggested by simulation in Ecotect for three cases (four scenarios).